Identidade cultural gaúcha nos usos sociais da internet: um estudo de caso sobre a página do gaúcho - Brignol, Liliane Dutra (Universidade do Vale do Rio dos Sinos, 2004)
The research aims the investigation of the relations that occur between the Internet and the Gaucho’s cultural identity, through a study case, from the concept of communication, culture and identity based on cultural studies. The study shall discuss how identity matters go beyond a site called “Página do Gaúcho”, which targets, through emphasis in the tradition, the thematic of the regional culture. The investigation shows the Gaucho’s identity as a mediator to social uses in the Web, at the same time that has another configuration through the media construction using an ethnographical approach joined with methodological procedures such as observation, life experience, productive routine and content analysis. The Internet, as a means of amplifying the experience of identity strategies, is increasing the possibilities of experimenting the ways of “to be gaucho” with the updating of the dispute that is found in the core of the identity. At the same time, it promotes reorganization from the adoption of communicative possibilities, forming virtual communities and changes in relations between uses and production.
Keywords: Internet; Identidade cultural gaúcha; Usos sociais das mídias; Gaucho’s cultural identity; the social uses of the media; ACCNPQ::Ciências Sociais Aplicadas::Comunicação